Soil/Air Partitioning of Semivolatile Organic Compounds. 1. Method Development and Influence of Physical−Chemical Properties - Hippelein, Martin; McLachlan, Michael S (Environmental science & technology, 1998)
Soil is the primary sink of semivolatile organic compounds (SOCs) in the terrestrial environment, while the atmosphere is the primary vector of these substances to humans via the agricultural food chain. Hence, the exchange of SOCs between soil and air is of paramount importance to their environmental fate and potential risk to humans. In this paper, a method is developed to determine soil/air partition coefficients (K SA) of SOCs. On the basis of the solid-phase fugacity meter developed for plants, the method was initially tested using a soil contaminated in the laboratory with chlorinated benzenes, polychlorinated biphenyls, and polycyclic aromatic hydrocarbons. A systematic validation exercise demonstrated that the method is not subject to a wide range of potential artifacts. It was then shown that K SA in moist soil (relative humidity = 100%) is independent of the water content of the soil. The method was then extended to the measurement of K SA in the original soil, which contained background levels of the SOCs. Good agreement was found between the K SA values measured with the original soil and with the labora tory contaminated soil, confirming that the studies with contaminated soil can be extrapolated to environmental conditions and demonstrating that it is possible to directly measure K SA at current background levels of soil contamina tion. The K SA values of the compounds studied ranged over almost 4 orders of magnitude. There was an excellent linear relationship between K SA and the quotient of the octanol/water and air/water partition coefficients (K OW/K AW), indicating that the Karickhoff model commonly applied to soil/water partitioning can be extended to the soil/air system. An equally good regression was obtained between K SA and measured octanol/air partition coefficients (K OA).